Crime counteraction within the scope of network approach - Lytvynov, Oleksii; Spitsyna, Hanna (Archives of Criminology and Forensic Sciences, 2021)
Network management is a relatively new concept, which, nevertheless, has taken its place in the field of science and practice of crime counteraction management. In connection with recognition of the place and role of networks in implementing management activity, a number of theoretical questions on redefining the role of state, legitimacy of network structures, trust to new forms of interaction within the state, private sector, nonprofit organizations and associations of citizens arise. The issue of state sovereignty, legitimacy and trust in the context of management problems are studied not only by political scientists, but also by criminologists who conduct research on the problems of improving the policy of crime counteraction. The majority of autonomous, independent and not subordinate to each other entities are involved, each of whom solves his task in this common problem by his own means and methods in accordance with corresponding legislation. However, no matter how independent and autonomous the participants in crime counteraction are, their division is unacceptable since each of them is only one part of the common state and legal system aimed at ensuring resolution of a single task in crime counteraction. Each of them, no matter how it works, is not able to address the issue of crime idependently, only by his own means. They only complement each other, and therefore their activity, undoubtedly, require organization, management, coherence, interaction, coordination. And one of the ways to organize the system of accomplishment of set tasks is network management. The peculiarities of the latter are that a certain part of crime counteraction happens primarily on a procedural basis, and law enforcement agencies are procedurally independent and autonomous (this excludes any authroitative forms of management). Therefore, network management is implemented only on the basis of equality of all its elements, independence of each of them when performing tasks, responsibility for their realization and compliance with law.